1970
DOI: 10.1111/j.1399-3054.1970.tb06425.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Heat Resistance of Thermophilic Bacteria

Abstract: The importance of inorganic ions for the heat stability of thermophilic bacteria was investigated. Cells of Bacillus stearothermophilus, strain 1503, were incubated at elevated temperatures in various media and the number of surviving organisms was determined at suitable intervals. The bacteria rapidly died at temperatures ordinarily employed for their cultivation if the surrounding medium lacked calcium ions. Besides calcium ions, potassium and phosphate ions and glucose, or some other energy source, seemed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…Calcium was over three times more effective than equivalent concentration of Na+ in reducing K+ efflux from the bulb scale tissue (Table I). This is consistent with the general protective effect of Ca2" on many cellular processes during stress (5,8,10,12) and postulated role of Ca2+ on the maintenance of membrane integrity (9).…”
Section: Discussionsupporting
confidence: 70%
“…Calcium was over three times more effective than equivalent concentration of Na+ in reducing K+ efflux from the bulb scale tissue (Table I). This is consistent with the general protective effect of Ca2" on many cellular processes during stress (5,8,10,12) and postulated role of Ca2+ on the maintenance of membrane integrity (9).…”
Section: Discussionsupporting
confidence: 70%
“…The Arrhenius plot in fig.4 indicates that the Thus calcium appears to be taken up by living calcium uptake rate increases with temperature, in cells at a rate which increases with temperature. In accordance with the higher demand for calcium at the light of earlier results [6,7] that calcium is needed for survival at high temperatures, we conclude that calcium is not just accumulated as a consequence of, but is indeed required for thermophilic growth of B. stearothermophilus.…”
Section: Resultssupporting
confidence: 64%
“…However, calcium, potassium, phosphate and an energy source were found to be necessary requirements for the survival of Bacillus stearothermophilus cells at elevated temperatures [6]. This finding suggests that an active transport of calcium ions into the cells is of fundamental importance for the heat stability of thermophilic bacteria.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The importance ofintracellular Ca 2+ in bacterial homeostasis is further supported by the work of Ljunger and Stahl (102,5), who suggested that the uptake of Ca 2+ into bacterial cells is of fundamental importance to the heat stability of thermophilic cells. The existence of a transport system for Ca 2+ was shown during vegetative growth of B. stearothermophilus (5).…”
Section: Role Of Ca 2+ In Bacterial Cellsmentioning
confidence: 91%